Store experiences and their influence on store performance and brand strength: Case Samsung Experience Store - Vanhanen, Iida (My University, 2014)
Experiential marketing is increasingly seen as a new magical key to consumers’ hearts. Brands are turning brick-and-mortar stores into state of the art retail spaces where memorable experiences and strong brand relationships are hoped to be born. Around the globe, several brands have opened up a special format of stores – the experience store. Although many speculations on the positive effects of experiences have been presented, few studies have provided empirical, quantified evidence for the link between store experiences and brand success. In consequence, research was needed to find out whether experience stores truly are so special. The purpose of this thesis was to investigate whether store experiences are capable of building brands and influencing store performance. For this purpose, empirical research was conducted in the Samsung Experience Store Helsinki. As main constructs of the study, store experience, brand equity, store performance, and product class involvement were measured, along with relevant background variables. Data was collected with an electronic survey from actual customers of the store, resulting in a sample of 131 respondents. Partial least squares structural equations modeling (PLS) was used for the analysis of the research model. Also, regression analysis was conducted to account for mediation and moderation effects. The results showed that store experiences do positively influence first, store performance, and second, separate dimensions of brand equity (that is, brand awareness, brand personality, and brand loyalty). Also, the effect of store experiences on store performance was found to be mediated by brand equity. Interestingly, customers’ product class involvement was detected to moderate the effect of store experience on store performance. That is, those who were highly involved with electronics had greater store experiences, and also displayed a stronger linkage between store experience and store performance. The results encourage marketers to continue with efforts to create great experiences for their customers. Experience stores can – and should be seen – as both powerful brand building tools and profitable sales channels. The creation of exceptional experiences can act as an important function of physical stores in the face of severe online competition.